Spinel LiMn2O4 cathode and carbonaceous anode material for electrochemical energy storage lithium-ion battery - Zahoor, Ahmed (2021)
Battery technology is one of the most promising technology for next-generation portable electronics, electric vehicle (EV), hybrid electric vehicles (HEV) and stationary energy storage systems. In this aspect, Li-ion batteries are the most attractive power-source candidate due to their superior high energy density as a comparison to the available rechargeable batteries. High energy density mainly depends on a high voltage and high specific capacity. Novel electrode materials research, specifically cathode plays an essential role in the development of advanced lithium-ion batteries. The electrochemical performance of active electrode material mainly relies on the crystal size and morphology. In the present study, various nanostructured cathode materials were synthesized to improve the energy density by using sol-gel assisted pechini, coating and ball milling techniques. Research reveals that nanomaterial-based cathode materials are preferable due to various advantages such as dimension reduction, faster ionic (Li+) and electronic (e-) transport and mechanical stability as compared to traditional solid-state synthesis-based materials. First, spinel-based cathode LiMn2O4 and carbon composite were studied in Li-ion battery application due to eco-environment, natural abundance, low cost with high operating potential, theoretical capacity and power density properties. In this work, step potential electrochemical spectroscopy (SPECS)/galvanostatic intermittent titration technique (GITT) is conducted on three-electrode systems, including spinel prepared by solid-state and sol-gel methods. SPECS experimental data has been fitted with planar, double planar, spherical, and Cottrell diffusional model, to elucidate the diffusional mechanisms and obtain accurate diffusivities for these materials. Theoretical models clearly illustrate that both spherical and double plane diffusion models are in excellent agreement with experimental data. LMOSS exhibits better diffusivity, with an average diffusivity closer to 10-13 -10-11 cm2/s as compared to 10-13-10-9 cm2/s for LMOSG. This work aims to develop a more comprehensive analysis technique for future work. The crystal structure, materials morphology and elemental composition were characterized by x-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), energy dispersive x-ray spectroscopy (EDS), and high-resolution transmission electron microscopy (HR-TEM). These experiments reveal the potential benefits of understanding Li-ion diffusion of spinel LiMn2O4 for high-power lithium-ion batteries (LIBs) storage performance. Secondly, anion substitution of fluorine into spinel cathode material was designed by using the sol-gel assisted pechini method. Fluorinated based spinels show better electrochemical performance as compared to pristine spinel. The fluorine doped spinels LiMn2O3.8F0.2 and LiMn2O3.9F0.10 showed improved capacity retention of around 94% and 90% respectively as compared to 90% for the pristine LiMn2O4 at 0.1C. Finally, Electrolytic reduction of molten carbonates (Li/K/Na) has been suggested as a practical approach improving the performance of lithium-ion batteries as anode material. Herein, novel carbonaceous materials were synthesized by using molten carbonates as an exciting new method of producing tuned carbons for battery applications. The electrodeposited carbon anode displays the highest specific capacity with 334 mAh g-1 at 0.1 C with coulombic efficiency of 95.70% and 255 mAh g-1 at 1C with a capacity retention (coulombic efficiency) of 85.8 % (100%) after 100 cycles in the potential window of 0.01-2V (vs Li/Li+). The electrochemical properties as measured using Galvanostatic charge-discharge, cycle ability, rate performance, cyclic voltammetry and electrochemical impedance spectroscopy were observed to be greatly enhanced by using the carbonate-derived anode as compared to the commercial graphite.